2018
DOI: 10.3390/nu10070913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pilot School-Based Nutrition Intervention on Dietary Knowledge, Attitudes, Behavior and Nutritional Status of Syrian Refugee Children in the Bekaa, Lebanon

Abstract: This study evaluated the impact of a 6-month school nutrition intervention on changes in dietary knowledge, attitude, behavior (KAB) and nutritional status of Syrian refugee children. A quasi-experimental design was followed; Syrian refuge children in grades 4 to 6 were recruited from three informal primary schools (two intervention and one control) located in the rural Bekaa region of Lebanon. The intervention consisted of two main components: classroom-based education sessions and provision of locally-prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 42 publications
5
79
1
1
Order By: Relevance
“…In another metaanalysis on physical activity and nutrition outcomes, the evidence indicated that interventions showed an average reduction in BMI of 0•11 kg/m 2 , yet the only nutrition study included in the review did not show any intervention effect on BMI (23) . As has been noted in previous reviews, the inconsistent evidence of intervention effect on anthropometry may be attributed to baseline malnutrition status or to the short duration of many of the interventions (18,33) . Thus, we might expect to see effects on outcomes such as weight gain even with shorter study durations and on height gain with longer durations (33) .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In another metaanalysis on physical activity and nutrition outcomes, the evidence indicated that interventions showed an average reduction in BMI of 0•11 kg/m 2 , yet the only nutrition study included in the review did not show any intervention effect on BMI (23) . As has been noted in previous reviews, the inconsistent evidence of intervention effect on anthropometry may be attributed to baseline malnutrition status or to the short duration of many of the interventions (18,33) . Thus, we might expect to see effects on outcomes such as weight gain even with shorter study durations and on height gain with longer durations (33) .…”
Section: Discussionmentioning
confidence: 92%
“…Since children spend a substantial proportion of their lives in the school setting, from a public health perspective, it makes sense to make schools as healthy as possible. Schools can offer an optimal setting to promote healthy eating habits (16)(17)(18)(19)(20) . They can provide a unique system for the delivery of cost-effective public health interventions since they have a large reach over the child population (21) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, search terms such as: "nutrition interventions in primary schools" and "Nutrition education interventions in school" were used in the Cochrane Library database to find the articles. In addition, reference lists of all retrieved articles and review articles [34] were screened for potentially eligible articles. The search strategy was initially developed in PubMed and adapted for use in other databases.…”
Section: Literature Searchmentioning
confidence: 99%
“…A person with a habit of eating diverse foods can maintain a normal nutritional status. Hudayani and Harake state that providing education and nutrition counselling with a comprehensive and continuous educated media can change the behaviour and habits of a person [27].…”
Section: Table II Cross Tabulation Between Knowledge Of Breakfast Andmentioning
confidence: 99%